Research to inform health systems' responses to rapid population ageing: a collection of studies funded by the WHO Centre for Health Development in Kobe, Japan - Megumi Rosenberg; Shinichi Tomioka; Sarah Louise Barber (BMC, 2022)
Abstract Population ageing is a global phenomenon that has profound implications for all aspects of health systems development. Research is needed to understand and improve the health system response to this demographic shift, especially in low- and middle-income countries where the change is happening rapidly. This Supplement was organized by the WHO Centre for Health Development in Kobe, Japan (WHO Kobe Centre) whose mission is to promote innovation and research for equitable and sustainable universal health coverage considering the impacts of population ageing. The Supplement features 10 papers all based on studies that were funded by the WHO Kobe Centre in recent years. The studies involve a diverse set of 10 countries in the Asia Pacific (Cambodia, Japan, the Lao People's Democratic Republic, Malaysia, Mongolia, Myanmar, the Philippines, Singapore, Thailand and Viet Nam); address various aspects of the health system including service delivery, workforce development and financing; and utilize a wide range of research methods, including economic modelling, household surveys and intervention evaluations. This introductory article offers a brief description of each study's methods, key findings and implications. Collectively, the studies demonstrate the potential contribution that health systems research can make toward addressing the challenges of ensuring sustainable universal health coverage even while countries undergo rapid population ageing.